Timber production and carbon storage in coffee with cedar (Cedrela adorata) and mahogany (Swietenia macrophylla) in Honduras - Jiménez Nehring, Nolvia Gabriela (2012)
Tesis (Mag. Sc) -- CATIE, Turrialba (Costa Rica), 2012